Peran Keselamatan dan Kesehatan Kerja Dalam Meningkatkan Kinerja Karyawan Perusahaan PT. Waru Gunung - Ike Novia Ardiana; Muzayyanatun - Ni'mah; Nabilah Rizki Amalia; Soffy - Balgies (Universitas Muhammadiyah Tangerang, 2023)
Human behavior is the main key to the risk of work accidents. This research has a purpose, namely to find out whether the role of occupational safety and health can affect the performance of employees at the company PT. Waru Gunung. The research used the method used, namely qualitative with descriptive analysis. Data obtained through direct interviews with the manager and employees of PT. Waru Gunung. Thus it can be conculded that the role of occupational safety and health is very influental in improving employee performance at the PT. Waru Gunung company.